STERILISASI EKSPLAN DAN SUB KULTUR ANGGREK, SIRIH MERAH DAN KRISAN PADA PERBANYAKAN TANAMAN SECARA IN VITRO - Elfiani, Elfiani; Jakoni, Jakoni (DINAMIKA PERTANIAN, 2017)
Subculture is one of stages to produce plant through tissue culture. Basically, subculture is to cut, cleave, and replant explant that grows for increasing number of plants. The purpose of this research is to sterilization a part of pant from field which will be used as explant and to make sub-culture on a part of plant to produce in vitro. Generally, the explant sterilization of orchid fruit and Red Betel Vine produces under satisfaction because of up to 90% of explant experiences contamination by fungus, bactery and browing. Sub-culture krisan on callus medya shows that a small number of culture successed to form callus, while other ones experiences contamination. On krisan sub-culture in bud medya is obtained a good result and differ significantly with others under a high level of contamination. All of those are likely caused by unskill in creating a sterile condition in the explant sterilization practices as well as at time in making sub-culture.